Collateral damage [videorecording] - Davis, Andrew; Reuther, Steven ([S.l.] : Warner Bross Video, 2001)
Officials investigating a terrorist bombing warn Gordy Brewer not to get involved, but events have already involved him in the most horrible way. His wife and child are among the victims claimed by the blast. Nail-biting excitement and bold one-man heroics fuel the powerful thriller Collateral Damage. Super-star Arnold Schwazenegger plays that one man. He's Brewer, a Los Angeles fireman who sets out to find the elusive terrorist known as El Lobo. Andrew Davis (The Fugitive) directs, deftly pacing the action as Brewer stalks his prey from L.A. to the jungles of Colombia to the power corridors of Washington DC. Brewer knows El Lobo will strike there. But how? When? And precisely where? in the feverish scramble for answers, one thing is clear; Collateral Damage is a ticking time bomb of suspens.
Screenplay, David Griffiths, Peter Griffiths ; music, Graeme Revell ; director of photograph, Adam Greenberg
Cast: Arnold Schwarzenegger (Gordy Brewer)
Keywords: Prison films; Canadians -- Foreign countries -- Drama